Potencial de ocorrência de avarias ambientais em bacias hidrográficas com ocupação rural mediante análise morfométrica - Manfré, Luiz Augusto [UNESP]; Ronquim, Flavia Marini [UNESP]; Ogihara, Vanessa Honda [UNESP]; Silva, Alexandre Marco da [UNESP]; Urban, Rodrigo Custódio [UNESP] (My University, 2010)
The understanding of the geo-morphological characteristics allows the identification of flood areas and instability slopes among others important features for land use planning. The study of the hydrological net and the analysis of morphometric parameters help in the geomorphologic characterization, providing specific physics indicators that quantify the risks for environmental damages. The present work used Geographic Information Systems (GIS) and carried out the morphometric analysis of two watersheds in the Alto Rio Sorocaba, municipality of Ibiuna (SP). Using digitalized topographic bases in the scale 1:50,000, the main morphometric parameters were extracted and the Digital Elevation Model (DEM) was obtained. Hence the slope, ground illumination, hill orientation and relief feature maps were elaborated. The characteristics for the two watersheds were quite similar, both have low risks for floods and landslides. Therefore, the concave feature is the predominant hill shape for both watersheds. The morphometric parameters directly related to the river density of the watersheds showed some differences, because the Sorocabuçú watershed presents higher value, resulting in a higher level of relief development. Thus, with this characterization it is possible to provide subsidies for environmental planning actions to the area.

A compreensão das características geomorfológicas possibilita a identificação de áreas alagáveis, encostas instáveis ou outras feições de importância no contexto do planejamento do uso da terra. O estudo da rede hidrológica e a análise de parâmetros morfométricos auxiliam na caracterização da geomorfologia, provendo indicadores físicos específicos, que quantificam, entre outros parâmetros, riscos a ocorrência a avarias ambientais. O presente trabalho utilizou ferramentas de Sistemas de Informação Geográfica (SIG) para prover análise morfométrica de duas bacias hidrográficas do Alto Rio Sorocaba, no município de Ibiuna (SP). A partir da digitalização de cartas topográficas na escala 1:50.000, foram extraídos os principais parâmetros morfométricos das bacias e gerados Modelos de Elevação Digital (MED), que possibilitaram a elaboração dos mapas de declividade, iluminação do terreno, orientação das vertentes e formas do relevo. As características encontradas para as duas bacias foram muito semelhantes, sendo que ambas possuem baixo risco de enchentes e deslizamentos. Além disso, nas duas bacias foi encontrada predominância de vertentes com geometria côncava. Os parâmetros morfométricos diretamente relacionados com a densidade de drenagem das bacias mostraram algumas diferenças, pois a bacia do rio Sorocabuçú apresenta valor maior, tendo como conseqüência maior grau de desenvolvimento no entalhamento do relevo. Desta forma, a partir desta caracterização é possível subsidiar ações de planejamento ambiental para a região.
Potential of occurrence of environmental damage in watersheds with rural land use through morphometric analysis
Keywords: Alto Sorocaba river; Environmental planning; Geographic information |Morphometric analysis; Alto Sorocaba; Análise morfométrica; Planejamento ambiental; Sistemas de informação geográfica